Pemungutan Retribusi Pasar Desa Dalam Rangka Menambah Pendapatan Asli Desa - Muhammad Azharuddin Fikri (Jurist-Diction, 2022)
AbstractThe village chief as the party who holds the power of village financial management can maximize the village's original income through the management of village assets, one of which is through the management of the village market. However, in practice it is not uncommon for problems such as the determination of the amount of retribution that is not in accordance with the legality of government acts. This study tries to examine the extent to which the authority of the village chief in collecting village market retributions as well as his responsibilities and accountability in case of abuse of authority or poor management. This research is a normative study using a statute approach, conceptual approach, and historical approach. Based on the analysis conducted, Law No. 6 of 2014 along with its derivative laws and regulations attributively states that the village government has the authority to manage village markets as well as to collect retributions for the use of village markets. The authority of the village government to collect retributions is only limited to what has been stipulated in village regulations. In addition, the village chief is also the party responsible and accountable if something goes wrong in the management of village market retributions. Keywords: Village Government; Village Market; Village Retributions. AbstrakKepala desa sebagai pihak yang memegang kekuasaan pengelolaan keuangan desa dapat memaksimalkan pendapatan asli desa melalui pengelolaan aset desa, salah satunya ialah melalui pengelolaan pasar desa. Namun dalam pelaksanaannya tidak jarang terjadi permasalahan seperti penetapan besaran retribusi yang tidak sesuai dengan keabsahan tindakan pemerintah. Penelitian ini mencoba menilik sejauh mana kewenangan kepala desa dalam memungut retribusi pasar desa serta tanggung jawab dan tanggung gugatnya apabila terjadi penyalahgunaan wewenang atau pengelolaan yang kurang baik. Penelitian ini merupakan penelitian normatif dengan menggunakan pendekatan perundang-undangan, pendekatan konsep, dan pendekatan historis. Berdasarkan analisis yang telah dilakukan, UU No. 6 Tahun 2014 beserta peraturan perundang-undangan turunannya secara atributif menyatakan bahwa pemerintah desa memiliki kewenangan dalam mengelola pasar desa sekaligus memungut retribusi atas pemanfaatan pasar desa. Kewenangan pemerintah desa untuk memungut retribusi hanyalah sebatas pada yang telah ditetapkan dalam peraturan desa. Selain itu kepala desa pulalah pihak yang bertanggungjawab dan bertanggung gugat jika terjadi kesalahan dalam pengelolaan retribusi pasar desa.Kata Kunci: Pemerintahan Desa; Pasar Desa; Keuangan Desa.